2016
DOI: 10.5115/acb.2016.49.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study on mandibular foramen and incidence of accessory mandibular foramen in mandibles of south Indian population and its clinical implications in inferior alveolar nerve block

Abstract: The mandibular foramen is a landmark for procedures like inferior alveolar nerve block, mandibular implant treatment, and mandibular osteotomies. The present study was aimed to identify the precise location of the mandibular foramen and the incidence of accessory mandibular foramen in dry adult mandibles of South Indian population. The distance of mandibular foramen from the anterior border of the ramus, posterior border of the ramus, mandibular notch, base of the mandible, third molar, and apex of retromolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
1
26
2
1
Order By: Relevance
“…So the knowledge of morphometry of ramus and the distance of mandibular foramen from the various borders of the ramus will be helpful in the surgeries of maxillofacial region for accurate localization of mandibular foramen and mandibular canal. In a study, in American white and Negros, Giles 7 mentioned that the parameters of mandibular ramus like height, minimum and maximum breadth are very important with classification accuracy of 85% 8 .The author Kilarkaje 9 et al in his study found mandibular foramen within the distance of 25mm from the anterior border, mandibular notch and third molar tooth and stated that there was bilateral symmetry in all the cases he studied while the author Shalini 5 found bilateral symmetry within the range of 13 to 20 %. On further review of literature, we found following results-As per A.C. Gabriel 14 the width of ramus and the position of mandibular foramen are interrelated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…So the knowledge of morphometry of ramus and the distance of mandibular foramen from the various borders of the ramus will be helpful in the surgeries of maxillofacial region for accurate localization of mandibular foramen and mandibular canal. In a study, in American white and Negros, Giles 7 mentioned that the parameters of mandibular ramus like height, minimum and maximum breadth are very important with classification accuracy of 85% 8 .The author Kilarkaje 9 et al in his study found mandibular foramen within the distance of 25mm from the anterior border, mandibular notch and third molar tooth and stated that there was bilateral symmetry in all the cases he studied while the author Shalini 5 found bilateral symmetry within the range of 13 to 20 %. On further review of literature, we found following results-As per A.C. Gabriel 14 the width of ramus and the position of mandibular foramen are interrelated.…”
Section: Discussionmentioning
confidence: 98%
“…In case of non -fusion of these divisions, the unfused divisions or rami (40% of cases) pass through different foramina which are called as accessory mandibular foramina. 5 According to Anand Reddy 6 , accessory mandibular foramina not necessarily pass sensory nerve elements always sometimes instead of nerves they pass blood vessels only. Therefore, the presence of accessory mandibular foramina is not always associated with difficulty in inferior alveolar nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…quienes encontraron una mayor presencia a nivel vestibular 14 . La mayor frecuencia del foramen en estas ubicaciones limita el análisis radiográfico durante el tratamiento de conductos; esto debido a que la ubicación del foramen apical en radiografías es alterada por la superposición de tejidos 15 . La ubicación vestibular o palatina no sería perceptible a través de radiografías, lo que dificultaría la localización del foramen apical.…”
Section: Discussionunclassified
“…Alves and Deana (2014) provided illustrations of a huge AMF. Samanta et al (2013) found it in 16.66% of mandibles and Shalini et al (2016) in 32.36%. Such a foramen can be named the juxta-mandibular (juxta-inferior alveolar) foramen.…”
Section: Accessory Mandibular Foramina: a Trivial Research?mentioning
confidence: 97%